Lessons from a private urban health centre in South India on why private healthcare system must step up cervical cancer screening - Rahman, Sajitha M. F.; Sankarapandian, Venkatesan; Antony, Jojin Eby; Pricilla, Ruby A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A 32-year-old frail mother of two children, 10 and two-year olds, presented to the urban health center in January 2025 with worsening white discharge per vaginum, significant weight loss, and back pain for three months. A vaginal examination revealed an ominous friable cervical lesion that bled profusely. Biopsy confirmed the diagnosis of poorly differentiated cervical cancer. Her only known risk factor was lower socioeconomic status. She was last seen by a health care professional three months ago for the same complaint and had the intrauterine device (IUCD) removed. A supportive husband and family decided to shift her care to a nearby cancer center in the government health system.